Blade Coating: Determination of Solvent Systems for Blade Coating Thin Film Photovoltaics (Adv. Funct. Mater. 22/2015). (June 2015) - Tait, Jeffrey G.; Merckx, Tamara; Li, Wenqi; Wong, Cindy; Gehlhaar, Robert; Cheyns, David; Turbiez, Mathieu; Heremans, Paul
Abstract : A five‐step procedure to develop solvent systems for thin film photovoltaic materials is described on page 3393 by P. Heremans and co‐workers. A combination of wettability studies, toxicological insights, and Hansen solubility parameters analysis lead to suitable inks. Organic photovoltaic devices are blade coated from several new diketopyrrolopyrrole‐based inks, and achieve equal performance to those from halogenated solvents.